2019
DOI: 10.2147/jaa.s193744
|View full text |Cite
|
Sign up to set email alerts
|

<p>Correlation between impulse oscillometry parameters and asthma control in an adult population</p>

Abstract: Purpose: Impulse oscillometry (IOS) has been proposed as an alternative test to evaluate the obstruction of small airways and to detect changes in airways earlier than spirometry. In this study, we sought to determine the utility and association of IOS parameters with spirometry and asthma control in an adult population. Patients and methods: Adults 14–82 years of age with asthma were classified into uncontrolled asthma (n=48), partially controlled asthma (n=45), and controll… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
13
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(16 citation statements)
references
References 36 publications
(31 reference statements)
2
13
0
Order By: Relevance
“…They found associations between oscillometric values and spirometry. 27 Similar data was published by Galat et al 44 in a review article on asthma control. Carr et al 45 reviewed literature on the correlation between small airways disease and asthma control, concluding that diagnose of SAD (small airway disease) can occur with various non-invasive tests, including oscillometry, and may improve treatment response.…”
Section: Clinical Applicationssupporting
confidence: 75%
See 1 more Smart Citation
“…They found associations between oscillometric values and spirometry. 27 Similar data was published by Galat et al 44 in a review article on asthma control. Carr et al 45 reviewed literature on the correlation between small airways disease and asthma control, concluding that diagnose of SAD (small airway disease) can occur with various non-invasive tests, including oscillometry, and may improve treatment response.…”
Section: Clinical Applicationssupporting
confidence: 75%
“…Studies showed that FOT has more sensitivity than spirometry in the case of children as a predictor of asthma and response to treatment. 16 , 27 When evaluating BD response, King et al 8 recommend the definition of a positive response as a decrease in Rrs5 with −40%, an increase in Xrs5 with +50% and decrease in AX with −80%. da Costa et al 28 studied the impedance changes after administration of salbutamol in the case of healthy and COPD patients, showing that oscillometric parameters are highly sensitive to broncho-dilatation, especially in early stages of COPD.…”
Section: Clinical Applicationsmentioning
confidence: 99%
“…We found that the differences shown by spirometry in older age groups were not present in resistance and reactance values measured by IOS. IOS measures airway impedance, which is a function of resistance and reactance, thus predicts about the peripheral airway obstruction and detects inspiratory and expiratory changes in airway resistance in asthmatic children 7,18,19 .…”
Section: Discussionmentioning
confidence: 99%
“…Airway resistance at different sound frequencies measure different parts of the airway. Measurements at low frequencies reflects both the central and peripheral airways while measurement at higher frequencies reflect the larger airways thus allowing prediction of the resistance and reactance of the small airways which are known to be primary area of involvement in asthma 6,7 .…”
Section: Introductionmentioning
confidence: 99%
“…However, another study concluded that IOS has no discriminative capacity to classify patients according to the degree of asthma control. 9 In the present study, we used a lower cut off for AX of 1.0 kPa/L using AOS as compared to 1.5 kPa/L using IOS in a previous study. 5 The reason for this is that AOS is more sensitive than IOS in detecting altered lung compliance.…”
Section: Word Count 1105mentioning
confidence: 99%